Reconstructing calcification in ancient coccolithophores: Individual coccolith weight and morphology of Coccolithus pelagicus (sensu lato) - Cubillos, Joana C.; Henderiks, Jorijntje; Beaufort, Luc; Howard, William R.; Hallegraeff, Gustaaf M. (Marine Micropaleontology, 2012)
International audience We have adapted an existing method to estimate coccolith calcite weight using birefringence (Beaufort, 2005) to suit the large coccoliths of Coccolithus pelagicus, which are only partially birefringent under cross-polarised light microscopy. Fossil and sediment trap material from the South Tasman Rise region of the Southern Ocean was used for calibration and validation. Our approach was tested with only the coccolith central area (CA) considered for measurement, to avoid relying on the less robust proximal shields. Thus our results are relative and intend to quantify intra-specific variations in volumetric calcite weight, expressed as a Weight Index (WI). Our results were overall consistent with mass estimation based on distal shield lengths. However, the WI approach clearly has the advantage in exploring allometric scaling between coccolith size and weight, as well as in measuring the degree of calcification in similarly sized morphotypes. Combining WI and morphometry data (distal shield length, DSL), we demonstrate subtle, but statistically significant changes in shape and thus calcification degree both within and between the tested Coccolithus populations. Most strikingly, it appears that modern Coccolithus populations in the Southern Ocean are, on average, more heavily calcified than their fossil counterparts. (c) 2012 Elsevier B.V. All rights reserved.